urgent algebra GCD Proof problem 1. The problem statement, all variables and given/known data let d=gcd(m,n). Prove that d=am+bn, where a,b are integers. 2. Relevant equations use of induction and euclidean algorithm. 3. The attempt at a solution i know when d being a generator and d=am+bn where m,n are generators, then d=gcd(m,n). But i got stuck when proving the converse(which is the problem statement above). I use the iterative algorithm(i.e. "n=qm+r";gcd(m,n)=gcd(m,r) and so on) but just does not work. And i do not know how to use "induction" in this proof. Thank you for helping me.